THE INCREMENT OF LEARNING IN THE SUBJECT OF ELECTRONIC OF THE COURSE OF ELECTRICAL ENGINEERING THROUGH THE APPLICATION OF THE CONCEPTS OF THE ANDRAGOGY IN FACULTY OF ELECTRICAL ENGINEERING (FIT) (Fiep Bulletin - online, 2011)
This paper intend to investigate and propose a revision of methodology for adult education to support Electronic in Electrical Engineer graduate at Faculdades Integradas Torricelli. The research is of the descriptive type and has as objective to collate the current pedagogical reality with the andragogic method, therefore being the pupil an adult individual, this would have to be coherent with the conditions pointed for the andragogical method as being necessary with respect to the success of the learning of the adults. A vision conservative indicates that and the methodology for use of the electronics laboratory restricts it anticipatedly the evidence of the theory showed in classroom. In contrast, based on board of abilities and skills are pointed in this paper that the topics of the content of program can be presented initially in the laboratory, and a time gotten the data for analysis, these will be used to put out and to awake the scientific questioning. Thus the observation and data gotten in the laboratory will be the base for the analyses, quarrels and better understood durin theory class because they reflect the common reality of the group.As a result is expected a better relation between education and learning with the same period of treatment of the program.
Keywords: Electronic; Andragogy; Social Psychology